1997
DOI: 10.1111/j.1365-2133.1997.tb03656.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous periarteritis nodosa: a clinicopathological study of 79 cases

Abstract: Cutaneous periarteritis nodosa (PAN) is a well-recognized entity characterized by tender subcutaneous nodules and livedo that may ulcerate. The pathogenesis of cutaneous PAN is not known. The objective of the study was to evaluate the clinical and histological features of 79 cases of cutaneous PAN and to investigate any clinical, pathological and immunological differences that may distinguish those cases likely to have a prolonged course. A retrospective analysis of 79 cases was conducted. Thirty-nine patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(21 citation statements)
references
References 21 publications
3
17
0
1
Order By: Relevance
“…7 An extensive retrospective study analyzing 79 cases of CPAN found that painful nodules on the lower extremities with associated swelling and edema were the most common clinical findings, found in 80% of the reported cases. 8 Other notable findings include livedo reticularis in 56%, skin ulcers in 49%, and tender indurated plaques in 10% of cases. 8 A subset of CPAN patients have also been described as presenting with atrophie blanche as the predominant skin finding in the absence of venous insufficiency.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…7 An extensive retrospective study analyzing 79 cases of CPAN found that painful nodules on the lower extremities with associated swelling and edema were the most common clinical findings, found in 80% of the reported cases. 8 Other notable findings include livedo reticularis in 56%, skin ulcers in 49%, and tender indurated plaques in 10% of cases. 8 A subset of CPAN patients have also been described as presenting with atrophie blanche as the predominant skin finding in the absence of venous insufficiency.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…8 Other notable findings include livedo reticularis in 56%, skin ulcers in 49%, and tender indurated plaques in 10% of cases. 8 A subset of CPAN patients have also been described as presenting with atrophie blanche as the predominant skin finding in the absence of venous insufficiency. 9 In our patient, the classic nodular presentation was absent, with only minimal swollen and firm areas over the feet.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Für milde Formen ohne Nekrosen und ohne Allgemeinzustandsverschlechterung und -symptomen kann eine topische Therapie mit Steroiden 24 und eine Kompressionstherapie eingeleitet werden. Bei schweren Formen und/oder ausgeprägten Schmerzen und Nekrosen stehen systemische Therapieoptionen wie die orale Steroidtherapie 25 , Methotrexat, Cholchizin, Hydroxychloroquin, Dapson oder Azathioprin 26 oder intravenöse Immunglobuline 27 zur Verfügung. Außerdem profitieren die Patienten von einer Therapie mit NSAR, welche nicht nur antiinflammatorisch sondern auch schmerzlindernd wirken 20 .…”
Section: Vaskulitiden Mit Kutaner Beteiligungunclassified
“…Although it is known that the peak of the onset of PAN is in the sixth decade of life and that PAN predominantly affects females, CA develops commonly in the fourth and fifth decades of life and predominantly affects males. Recent cohort studies reported a female-to-male ratio of 1.22–3.53 and that the mean or median age of onset was around the fourth decade of life ( Table 1 ) ( 7 , 10 15 ). Like PAN, CA also affects children.…”
Section: Epidemiologymentioning
confidence: 99%